VISUAL IDENTIFICATION OF DEFORMATION RELIEF AS WELL AS ESTIMATION OF THE ACCUMULATED FATIGUE DAMAGE - Карускевич, М. В.; Костенюк, Д. М.; Каран, Є. В (Science-based technologies, 2009)
Investigation of the surface deformation relief of alclad aluminum alloy D16AT under fatigue has been carried out. The possibility of deformation relief visual identification as well as estimation of the accumulated fatigue damage are proved.